2022
DOI: 10.3390/healthcare10040621
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Design of Vision Protection Products Based on Children’s Visual Fatigue under Online Learning Scenarios

Abstract: The rate of myopia in children is increasing rapidly under online learning scenarios. One of the important reasons for this is incorrect reading and writing posture. Three screen view parameters (viewing angle, viewing height, and viewing distance) are selected as significant influencing factors and blink rating is used as a sign of visual fatigue through literature analysis to study the influence factors of myopia in children, and their correlation. Children’s visual fatigue is evaluated by subjective evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
1
7
2
Order By: Relevance
“…Specifically, elementary, middle, and high school students, who spent more time on screens, exhibited significantly higher blinking rates than preschool and infant groups with shorter screen exposure. These findings align with those of Feng et al ( 3 ), suggesting that the intensity of daily near work was greater for elementary, middle, and high school students. However, during the initial hour of screen time, the blinking rate in each age group fluctuated only slightly, with no statistically significant differences.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Specifically, elementary, middle, and high school students, who spent more time on screens, exhibited significantly higher blinking rates than preschool and infant groups with shorter screen exposure. These findings align with those of Feng et al ( 3 ), suggesting that the intensity of daily near work was greater for elementary, middle, and high school students. However, during the initial hour of screen time, the blinking rate in each age group fluctuated only slightly, with no statistically significant differences.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of dry eye syndrome in children has reached 50–60%, and its symptoms include dry eyes, foreign body sensation, tears, blurred vision, headache, esotropia, and abnormal vision. A study of 52 children in grades 3–4 revealed that the level of asthenopia was lowest when the screen was approximately 50 cm from the eyes ( 3 ). Reid et al ( 25 ) proposed that children and adolescents follow the 20–20-20 principle while using digital products: rest and look at an object 20 feet away for 20 s after using the devices for 20 min.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensor is tilted away from the table at an angle of 28.35 degrees (tại sao). When the user is using the device, the system will sound an auditory warning when the distance between the user's head and the sensor is less than 30cm [29], urging them to return to the proper posture. The system is then equipped with a fine dust sensor, model number GP2Y1010AU0F [30], to track the level of fine dust in the user's learning environment.…”
Section: System Block Diagrammentioning
confidence: 99%